Micronutrient bioavailability: concepts, influencing factors, and strategies for improvement - Richards, James D.; Cori, Héctor; Rahn, Maike; Finn, Kristen; Bárcena, Juan; Kanellopoulos, Alexandros K.; Péter, Szabolcs; Spooren, Anneleen (Frontiers in Nutrition, 2025)
The human diet provides a range of macronutrients and micronutrients, which are metabolized for energy and used to support all aspects of life. The extent to which these nutrients are absorbed in a form that can be used by metabolic processes, or stored for later use, is termed bioavailability. Certain dietary factors increase the bioavailability of micronutrients: bioavailability can be enhanced by different vitamin forms (e.g., calcifediol is more bioavailable than cholecalciferol; methylfolate is more bioavailable than folic acid), and by the food matrix and nutrient interactions (e.g., fat increases absorption of fat-soluble vitamins; multiple vitamins support iron absorption and metabolism). Conversely, plant-based foods exhibit reduced micronutrient bioavailability, due to entrapment in cellular structures and binding by antagonists such as phytate and fiber. Host factors also impact micronutrient availability. A healthy gastrointestinal microbiota can increase the absorption of vitamins and minerals, and certain life stages (e.g., pregnancy and lactation) are characterized by increased absorptive capacity. In contrast, the elderly exhibit reduced ability to absorb certain vitamins, and bacterial overgrowth/dysbiosis can reduce the availability of several vitamins. Several medications reduce vitamin absorption and status. Reduced bioavailability, poor quality diets, lower micronutrient content in foods due to soil depletion and climate change, and decreasing micronutrient intakes lead to widespread, global deficiencies. This in turn contributes to higher prevalence of non-communicable diseases such as anemia, osteoporosis, cardiovascular disease, and blindness; decreased growth; impaired immunity and increased incidence of infections; and increased mortality rates. Strategies to improve bioavailability and nutrient status are crucial and align with United Nations Strategic Development Goals 2 and 3. Vitamins and minerals added to foods or taken as supplements generally are at least as bioavailable as those endogenously in foods, and often more so. In addition, certain technologies are available to further increase micronutrient bioavailability. These include permeation enhancers, lipid-based formulations, nutrient compounding/encapsulation, and phytase to increase bioavailability of minerals trapped by phytic acid. Solutions such as these will help supply highly absorbable and utilizable vitamins and minerals, help close widespread nutritional gaps, and support adequate nutritional status and optimal health across diverse populations worldwide.